Clinical Prediction Rules to Classify Types of Stroke at Prehospital Stage: Japan Urgent Stroke Triage (JUST) Score. Issue 8 (August 2018) - Uchida, Kazutaka; Yoshimura, Shinichi; Hiyama, Nagayasu; Oki, Yoshiharu; Matsumoto, Tsuyoshi; Tokuda, Ryo; Yamaura, Ikuya; Saito, Shin; Takeuchi, Masataka; Shigeta, Keigo; Araki, Hayato; Morimoto, Takeshi
Abstract : Background and Purpose—: Endovascular therapy is effective against acute cerebral large vessel occlusion (LVO). However, many patients do not receive such interventions because of the lack of timely identification of the type of stroke. If the types of stroke (any stroke, LVO, intracranial hemorrhage [ICH], and subarachnoid hemorrhage [SAH]) were to be predicted at the prehospital stage, better access to appropriate interventions would be possible. Japan Urgent Stroke Triage (JUST) score was clinical prediction rule to classify suspected patients of acute stroke into different types at the prehospital stage. Methods—: We obtained information for signs and symptoms and medical history of consecutive suspected patients of acute stroke at prehospital stage from paramedics and final diagnosis from the receiving hospital. We constructed derivation cohort in the historical multicenter cohort study from June 2015 to March 2016 and validation cohort in the prospective multicenter cohort study from August 2016 to July 2017. The derivation and the validation cohorts included 1229 and 1007 patients, respectively. We constructed multivariate logistic regression models with 21 variables to develop clinical prediction rules, which distinguish between different types of stroke: any stroke, LVO, ICH, and SAH. Results—: Among the 1229 patients (median age, 72 years; 55% men) in the derivation cohort, 533 stroke, 104 LVO, 169 ICH, and 57 SAH cases were observed. The developed rules showed that the areas under the receiver operating curves were 0.88 for any stroke, 0.92 for LVO, 0.84 for ICH, and 0.89 for SAH. The validation cohort of 1007 patients (median age, 75 years; 56% men) showed that the areas under the curves of any stroke, LVO, ICH, and SAH were 0.80, 0.85, 0.77, and 0.94, respectively. Conclusions—: These clinical prediction rules can help paramedics classify the suspected patients of stroke into any stroke, LVO, ICH, and SAH groups with excellent accuracy. Abstract : Supplemental Digital Content is available in the text.